Analisis asesmen Kurikulum Merdeka menggunakan model CIPP (Context, Input, Process, and Product) di SDN 2 Sukamulya - Dinda Nur Azizah; Agus Saeful Anwar (COLLASE (Creative of Learning Students Elementary Education), 2026)
Abstract This study aims to analyze the implementation of the Independent Curriculum assessment using the CIPP (Context, Input, Process, and Product) model at SDN 2 Sukamulya. The research problem arises from the importance of understanding the planning, implementation, and evaluation of assessments to improve student learning outcomes and support the philosophy of independent learning. The method used is descriptive qualitative with data collection techniques in the form of interviews, observations, and documentation of homeroom teachers and the principal. The results show that the assessment planning is in accordance with the principles of the Independent Curriculum, although teachers' understanding still needs to be improved. During the implementation stage, teachers began to consistently apply diagnostic, formative, and summative assessments with the support of various instruments. The evaluation showed a positive impact on student engagement and learning outcomes, although comprehensive and reflective assessment monitoring aspects are needed to achieve the objectives of the Independent Curriculum. Keywords: Independent curriculum, Curriculum assessment, CIPP Model Abstrak Penelitian ini bertujuan untuk menganalisis pelaksanaan asesmen Kurikulum Merdeka menggunakan model CIPP (Contect, Input, Process, and Product) di SDN 2 Sukamulya. Permasalahan penelitian muncul dari pentingnya pemahaman terhadap perencanaan, pelaksanaan, dan evaluasi asesmen guna meningkatkan hasil belajar peserta didik serta mendukung filosofi merdeka belajar. Metode yang digunakan adalah deskriptif kualitatif dengan tekhnik pengumpulan data berupa wawancara, observasi, dan dokumentasi terhadap guru wali kelas dan kepala sekolah. Hasil penelitian menunjukan bahwa perencanaan asesmen telah sesuai dengan prinsip Kurikulum Merdeka, meskipun pemahaman guru masih perlu ditingkatkan. Pada tahap pelaksanaan, guru mulai menerapkan asesmen diagnostik, formatif, dan sumatif secara konsisten dengan dukungan berbagai instrumen. Evaluasi menunjukan dampak positif terhadap keterlibatan dan hasil belajar siswa, meskipun aspek pemantauan asesmen yang komprehensif dan reflektif untuk mencapai tujuan Kurikulum Merdeka. Kata Kunci: Kurikulum Merdeka, Asesmen Kurikulum, Model CIPP